2015
DOI: 10.1007/s11046-015-9915-0
|View full text |Cite
|
Sign up to set email alerts
|

Development and Evaluation of a Novel Real-Time PCR for Pan-Dermatophyte Detection in Nail Specimens

Abstract: An accurate diagnosis of tinea unguium is necessary for the selection of antimycotics and successful treatment. To rapidly and accurately identify the aetiological agents causing tinea unguium, we improved upon the conventional boiling method for DNA extraction and developed a novel real-time PCR detection system that includes two assays. The two assays, based on the amplification of ribosomal internal transcribed spacer regions and 28S rDNA, were designed to detect pan-dermatophyte and Trichophyton rubrum, re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 21 publications
2
7
1
Order By: Relevance
“…The positive and negative controls in all experiment runs ruled out the possibility of experimental error. The sensitivity obtained for the real‐time PCR in our study (87.5%) was lower than observed in previous studies, in which the sensitivity ranged from 90.4% to 100% …”
Section: Discussioncontrasting
confidence: 91%
“…The positive and negative controls in all experiment runs ruled out the possibility of experimental error. The sensitivity obtained for the real‐time PCR in our study (87.5%) was lower than observed in previous studies, in which the sensitivity ranged from 90.4% to 100% …”
Section: Discussioncontrasting
confidence: 91%
“…Within this context, studies suggest that real-time PCR can be applied successfully for the diagnosis of dermatophytosis with much higher precision compared to classical diagnostic methods [48]. Furthermore, evaluating dermatophytes in nail samples, [66] showed that real-time PCR detected the presence of dermatophytes in samples that tested negative by conventional PCR, suggesting a higher diagnostic sensitivity of the former.…”
Section: Culture Microscopy Histology and Molecular Assays Based Onmentioning
confidence: 99%
“…In an attempt to increase the diagnostic response, real-time PCR can be performed as described by [67], who indicates multiplex RT-PCR as the fastest and most efficient method for the identification of dermatophyte species in clinical samples, or using pan-dermatophyte primers as described by [66] for the diagnosis of dermatophytes in nail samples. Commercial kits designed to facilitate the identification of dermatophytes by real-time PCR have also been developed.…”
Section: Culture Microscopy Histology and Molecular Assays Based Onmentioning
confidence: 99%
“…So, in the absence of a real gold standard, it is more reasonable to use some statistical methods such as LCA, which gives a possibility to calculate not only sensitivities but also specificities. In two studies, PCR was compared to direct microscopic examination and culture with LCA, and both its sensitivity and specificity were found to be over 80% …”
Section: Discussionmentioning
confidence: 99%
“…However, there is no real gold standard to calculate their sensitivities and specificities. So, latent class analysis (LCA) has been used to determine the value of PCR in the diagnosis of onychomycosis in comparison to direct microscopic examination and culture …”
Section: Introductionmentioning
confidence: 99%